Compressive Properties of Poly (Dimethylsiloxane)–Hollow Glass Microballoons Syntactic Foams. Issue 6 (November 2022) - Upadhyay, Alok; Ullas, AV
Polymer syntactic foams are lightweight polymer composites that are prepared by introducing hollow microspheres in a resin. The main endeavour is to obtain a significant reduction in the weight of the composite along with energy absorption. The present investigation aims to prepare poly (dimethylsiloxane) (PDMS)-hollow glass microballoons (HGM) (40–60% v/v) syntactic foams. Not only did HGM reduce the density of the syntactic foams but also act as a reinforcing phase and increase the compressive properties of PDMS. A ∼25% reduction in density was obtained in syntactic foam when compared to the neat elastomer. Similarly, an improvement of ∼118% in compressive strength was attained at 40% loading of HGM in PDMS. Specific compressive strength and toughness values also registered improvements of the order of ∼191 and ∼240% respectively which highlight the potential of PDMS syntactic foams in varied applications. Graphical Abstract